A histone deacetylase inhibitor, largazole, decreases liver fibrosis and angiogenesis by inhibiting transforming growth factor‐β and vascular endothelial growth factor signalling. (26th December 2012) - Liu, Yuqing; Wang, Zhuo; Wang, Jianing; Lam, Wingchi; Kwong, Shuqin; Li, Furong; Friedman, Scott L.; Zhou, Shuyan; Ren, Qi; Xu, Zhengshuang; Wang, XinGen; Ji, Ling; et al.
Abstract Background & Aims Largazole is a novel histone deacetylase (HDAC) inhibitor. This study investigated the effects of largazole against liver fibrosis. Methods The in vitro effects of largazole were examined using hepatic stellate cells (HSCs). In vivo effects of largazole were studied using a mouse liver fibrotic model induced by CCl4. Results Largazole augmented acetylation of histone H3 (H3) and histone H4 (H4) in HSCs. It directly inhibited the activation of HSCs owing to HDAC inhibitory activity as the antifibrotic effect of largazole was significantly decreased in cells with HDAC1, HDAC2 and HDAC3 knockdown. Largazole also induced apoptosis of HSCs. Largazole not only inhibited the expression of TGFβR2, but also reduced phosphorylation of Smad2 and Akt induced by TGF‐β1. Largazole also inhibited the expression of vascular endothelial growth factor (VEGF) and its receptor. VEGF‐induced proliferation of HSCs and activation of Akt and p38MAPK were also suppressed by largazole. In vivo, largazole reduced the expression of collagen I, α‐smooth muscle actin and tissue inhibitor of metalloproteinase‐1 in CCl4–induced fibrosis, and these antifibrotic effects were associated with increased acetylation of H3 and H4. Largazole also induced HSCs to undergo apoptosis in vivo, which was correlated with downregulation of bcl‐2 and bcl‐xL. Furthermore, largazole inhibited angiogenesis in vivo as evidenced by reduced expression of CD34, VEGF and VEGFR. In addition to its antifibrotic activity, the drug reduced inflammatory activity in CCl4‐induced liver fibrosis. Conclusions Our findings revealed a novel role of largazole in the treatment of liver fibrosis. Through multiple mechanisms, largazole could be a potentially effective antifibrotic agent.